Yiqi Huoxue Recipe Regulates Autophagy through Degradation of Advanced Glycation End Products via mTOR/S6K1/LC3 Pathway in Diabetic Nephropathy. (9th August 2021) - Chen, Liang; Dai, Linghao; Liu, Yi; Li, Xinyue; Wang, Hui
Abstract : Background . Yiqi Huoxue recipe can delay the progression of diabetic nephropathy, but its treatment mechanism is still unclear. We aimed to explore the effects of Yiqi Huoxue recipe on autophagy in diabetic nephropathy and its underlying mechanism. Methods . All rats were randomly divided into seven groups. The body weight, kidney weight, blood glucose, glycated hemoglobin, urine protein, urine microprotein, creatinine, urea nitrogen, triglyceride, and lipoprotein were analyzed. HE, Masson, and periodic acid-Schiff staining were used to detect the severity of pathological changes in kidneys. The level of advanced glycation end products was assessed by the ELISA. Immunofluorescence staining was performed to check the expressions of podocin and nephrin. The expression levels of mTOR/S6K1/LC3 pathway-related proteins and mRNA were detected by qRT-PCR and western blotting. Results . Yiqi Huoxue recipe significantly elevated body weight and significantly decreased kidney weight and kidney index. Yiqi Huoxue recipe significantly affected the levels of biochemical indicators in diabetic nephropathy and showed a regulatory effect on kidney damage and lipid metabolism disorders. ELISA showed that Yiqi Huoxue recipe significantly reduced the level of advanced glycation end products. The expressions of nephrin and podocin increased significantly, depending on the dosage of Yiqi Huoxue recipe. Additionally, Yiqi Huoxue recipe regulated the expression levels of p-AKT, mTOR, S6K1, and LC3. Conclusion . Yiqi Huoxue recipe regulates podocyte autophagy to promote the degradation of advanced glycation end products through mTOR/S6K1/LC3 pathway. It has a certain guiding significance for the diagnosis and treatment of diabetic nephropathy.